1967
DOI: 10.1111/j.1471-4159.1967.tb09497.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐chain Bases of Brain and Spinal Cord of Rabbits*

Abstract: IN RECENT years a number of investigators have reported the occurrence in mammalian tissue of long-chain bases other than sphingosine. Dihydrosphingosine was isolated from cerebrosides of beef brain and spinal cord by CARTER, HAINES, LEDYARD, and NORRIS (1947), from cerebrosides of human brain by SCHWARZ, DREISBACH, BARRIONUEVO, KLESCHICK and KOSTYK (1961), and from blood plasma by SWEELEY and MOSCATELLI (1959). The 20-carbon homologue of sphingosine was detected in sphingolipids of horse and beef brain by PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1968
1968
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…; Sonnino & Chigorno, BBA ) and increases with age in neurological diseases, whereas others found it in non‐complex sphingolipids as well but with a 50 : 50 ratio (Rosenberg and Stern ; Schwarz et al . ) for both chain lengths or even a much lower abundance of C20‐bases (Schwarz et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Sonnino & Chigorno, BBA ) and increases with age in neurological diseases, whereas others found it in non‐complex sphingolipids as well but with a 50 : 50 ratio (Rosenberg and Stern ; Schwarz et al . ) for both chain lengths or even a much lower abundance of C20‐bases (Schwarz et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…) for both chain lengths or even a much lower abundance of C20‐bases (Schwarz et al . ). Concerning non‐neuronal tissues, very scarce information on the abundance of C20‐sphingolipids is available.…”
Section: Discussionmentioning
confidence: 99%
“…8). Previous biochemical studies have revealed that the LCB of the brain ganglioside species has either 18 or 20 carbon atoms (i.e., C18-or C20-sphingosine), and C20-sphingosine (C20-LCB species) is present in significant amounts only in the central nervous system (Jungalwala et al 1979;Sambasivarao and McCluer 1964;Schwarz et al 1967;Sonnino and Chigorno 2000). Its content increases significantly in rodents and humans throughout life (Mansson et al 1978;Palestini et al 1990Palestini et al , 1991.…”
Section: Ims For Endogenous Metabolites: Gangliosidesmentioning
confidence: 96%
“…An increase with age of 20-carbon bases has been noted for gangiioside (59) and ceramide (40). A relatively high amount of d18:0 has been found in human peripheral nerve (40) and rabbit spinal cord (54), which confirms an earlier finding from bovine nerve tissue (62). Trihydroxy bases have not been found in nerve tissue, except for a trace amount in peripheral nerve sulfatide and in brain ganglioside (40).…”
Section: Distributionmentioning
confidence: 99%